Education and Fundamentalism - Burton, Ronald (Review of religious research, 1989)
The paper explores the relationship between education and Fundamentalism. It was hypothesized that these two variables would be negatively related. It was also expected that this negative relationship would be stronger among converts to Fundamentalism than among those raised as Fundamentalists. In addition, it was expected that Fundamentalism would relate differently to conservative social attitudes for people in different educational groups. The data came from a survey of Middletown residents [N = 379]. For the present study only the information from white, Protestant respondents was used [N = 281]. There was a weak, negative relationship between education and Fundamentalism. However, contrary to our expectations, converts to Fundamentalism were not less educated people. Finally, it was found that the Fundamentalist perspective differs by educational group.